PERANCANGAN SISTEM INFORMASI E-LIBRARY PADA SMA NEGERI 2 TARUTUNG BERBASIS WEB DENGAN TEKNOLOGI RESPONSIF - Sihotang, Vemmy Joshi Apfia; Harianja, Eva Julia Gunawati; Nainggolan, Rena (Universitas Methodist Indonesia, 2023)
Library data processing at SMA Negeri 2 Tarutung is still done manually. This is a problem of SMA N 2 Tarutung library, such as limited book collection, difficulty accessing books, inability to present information optimally in terms of speed, accuracy, and smooth system, and other problems related to traditional libraries. The purpose of this final project research is to design a web-based library for SMA Negeri 2 Tarutung that can be used to encourage students to read more books and make it easier for students to access books, namely through digital books (E-Library) Research methodology to collect information about library information system design includes reading scientific papers, conducting interviews, and making observations. Interviews and observations are used to analyze information system needs, which is then followed by creating databases, web inputs and outputs, and PHP software. The development phase includes PHP program development, database design, input and output design for the web, and Data Flow Diagrams (DFDs). Trials are run to assess the system as a whole. The results of the design of the E-library information system show that the application of this system can improve the quality of student reading by facilitating access to books through the web platform.